LEPIDIPTERAN PESTS OF SOYBEAN IN THE CONDITIONS OF THE RIGHT-BANK FOREST-STEPPE OF UKRAINE - Chykhrai, A. V.; Mostoviak, S. M. (Scientific Progress & Innovations, 2022)
In recent years, there has been a significant increase in sown areas under soybeans. This crop is a valuable food and fodder crop. Grain contains from 40 to 55 % of proteins that digested by humans and animals, up to 26 % of fats, about 30 % of carbohydrates and a significant amount of vitamins. Soybean crops on the globe occupy about 120 million hectares, and grain production has exceeded 300 million tons. Soybeans are the world's leading crop in terms of yield, it is about 30 kg/ha. To obtain high yields, it is necessary to use pest control systems. On the soybeans, develop about 114 species of pests that can significantly reduce its yield and grain quality. Therefore, the aim of our article was to review the literature on the harmfulness of lepidopteran pests that develop on soybean crops. Analysis of the literature showed that soybeans are harmful to almost all species, but the most numerous are Orthoptera, Hemiptera, Thysanoptera, Coleoptera, Lepidoptera, Diptera and Acariformes. At the same time, a great danger among the harmful soy entomocomplex in Ukraine is the complex of lepidipteran pests, which according to various data is about 40 % of the harmful soy entomocomplex. There is also evidence that due to global warming, the harmfulness of insects in crops of soybeans and other crops will only increase, there will be an expansion of their range. There is evidence that with increasing air temperature, lepidipteran pests and species diversity and numbers predominate in the soybean etomocomplex. The most dangerous species include Etiella zinckenella Tr., Margaritia sticticalis L., Vanessa cardui L. and a group of leaf-eating moths, namely Chloridea viriplaca Hfn., Helicoverpa Armigera Hfn., Autographa gamma L., Mamestra brassicae L., which are harmful to different years can range from 30% to 90% of crop yields. In addition, there are reports that in recent years, the dominant pest in soybean crops has become Vanessa cardui L., which previously did not harm. There is an expansion of the range of Vanessa cardui L. in Ukraine. Its appearance is observed in Polissya, the weather conditions of which are atypical for this butterfly. As we can see, the species composition and development of lepidipteran pests in soybean crops constantly varies, depending on weather conditions and the expansion of the range of harmful species of lepidipteran pests that have not previously harmed the crop. Therefore, our task is to record and monitor the harmful entomocomplex of soybeans, focusing on lepidipteran pests, which under favorable conditions can lead to significant crop losses.